Composite graphite material, preparation method thereof and battery
By using resin-coated graphite materials with a mass proportion of 15% to 30%, the problem of fast charging and storage performance of graphite materials in lithium-ion batteries is solved, and efficient electrochemical performance is achieved.
Patent Information
- Application Number
- CN202411948098.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-04
AI Technical Summary
The prior art is difficult to take into account both the fast charging and storage performance of graphite materials in lithium-ion batteries, and the coating of graphite by traditional soft carbon materials cannot take into account both the fast charging and storage capabilities.
A resin with a mass proportion of oxygen atoms is 15% to 30% as the graphite cladding material, and is coated on the surface of the graphite matrix material through a hard carbon precursor, and a composite graphite material is obtained after carbonization.
This method can significantly improve the fast charging performance and storage performance of composite graphite materials without sacrificing other electrochemical properties, and is suitable for large-scale industrial production.
Smart Images

Figure CN119750568A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrochemical devices and relates to a composite graphite material and a preparation method thereof and a battery. Background Art
[0002] Lithium-ion batteries are widely used in new energy and other fields due to their high energy density and excellent cycle performance. Graphite negative electrode materials are widely used in the field of lithium batteries due to their high specific capacity and environmental friendliness. However, the high crystallinity of graphite materials limits the rapid deintercalation and transmission of lithium ions between graphite layers, affecting the fast charging performance.
[0003] Based on this, the existing technology usually coats a layer of amorphous carbon material on the surface of graphite to prepare a carbon material with a core-shell composite structure to improve the fast charging performance of graphite. The traditional coating carbonization process uses soft carbon as a coating material. Although it can significantly improve the fast charging performance of the material, the storage performance of the negative electrode material after coating is deteriorated due to the large number of functional groups on the surface of amorphous carbon. If a high-temperature carbonization process is used, although it can reduce material defects and impurities, optimize the interface characteristics between the material and the electrolyte, and improve storage performance, the traditional coating material soft carbon is an easily graphitized carbon material. As the temperature increases, its disorder will decrease and the crystallinity will continue to increase, resulting in the deterioration of fast charging performance. Therefore, the coating of graphite by traditional soft carbon materials cannot take into account both fast charging and storage capabilities.
[0004] In order to solve the problems caused by soft carbon-coated graphite materials, current studies have found that graphite materials can be coated with hard carbon. Hard carbon is a type of carbon that is not easily graphitized, has a large interlayer spacing, abundant pores, a high specific surface area, and more defects. High-temperature carbonization can reduce its defects and impurities, and can further achieve a balance between fast charging and storage performance of graphite materials; however, due to the high specific surface area, defects and pores of hard carbon materials, the initial efficiency and cycle performance of the material are easily reduced.
[0005] Therefore, how to make graphite materials have both fast charging performance and storage performance without affecting the performance of other electrochemical properties is a technical problem that needs to be solved urgently. Summary of the invention
[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a composite graphite material, a preparation method thereof and a battery. The preparation method provided by the present invention selects a resin with a mass proportion of oxygen atoms of 15% to 30% as the coating raw material of graphite, and the obtained composite graphite material can well balance the fast charging performance and storage performance, and will not affect the normal performance of other electrochemical properties of the composite graphite material.
[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a method for preparing a composite graphite material, the preparation method comprising the following steps:
[0009] Coating a hard carbon precursor on the surface of a graphite substrate material to obtain a preliminarily coated graphite material, and carbonizing the material to obtain the composite graphite material;
[0010] Wherein, the hard carbon precursor comprises resin, and the mass proportion of oxygen atoms in the resin is 15% to 30%.
[0011] For example, the mass percentage of oxygen atoms in the resin can be 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29% or 30%, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0012] It should be noted that the present invention does not specifically limit the specific type of resin, and the present invention is applicable to any type of resin that can be used as a hard carbon precursor. For example, the resin includes but is not limited to at least one of epoxy resin, phenolic resin or polyfurfuryl alcohol resin, etc.; and the initially coated graphite material is the resin coated on the surface of the graphite matrix material.
[0013] In addition, the mass ratio of oxygen atoms in the resin can be obtained by conventional element content testing methods, such as organic element analyzer testing (EA).
[0014] The preparation method provided by the present invention can provide sufficient active sites to improve the lithium insertion kinetics by selecting a resin in which the mass percentage of specific oxygen atoms is 15% to 30% as the coating material of the graphite matrix material, while not having too many defect sites, so that the obtained composite graphite material of the hard carbon-coated graphite matrix material can take into account both fast charging performance and storage performance without sacrificing other electrochemical properties; the preparation method provided by the present invention is simple to prepare, does not require complicated processing procedures, and is more conducive to large-scale industrial production.
[0015] In the present invention, if the mass proportion of oxygen atoms in the resin is less than 15%, due to its relatively small functional groups, after high-temperature carbonization, although the storage performance can be improved, the active sites are insufficient, the lithium insertion channels are relatively few, and the fast charging performance is insufficient; and if the mass proportion of oxygen atoms is greater than 30%, there are too many surface functional groups, and the composite graphite material prepared by high-temperature carbonization coating will contain more defect sites. During the battery charge and discharge cycle, there are many side reactions, which increases the consumption of lithium ions, thereby resulting in a significant decrease in the first inventory efficiency, and it is also impossible to effectively improve the product's cycle performance and storage performance.
[0016] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.
[0017] Preferably, based on the mass of the initially coated graphite material as 100%, the mass of the resin accounts for 2% to 5%, for example, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0018] In the present invention, based on the mass of the initially coated graphite material being 100%, the mass of the resin accounts for 2% to 5%, which is more conducive to taking into account both fast charging performance and initial coulombic efficiency.
[0019] Preferably, the amount of residual carbon of the resin after carbonization is 25% to 35%, for example, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34% or 35%, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0020] In the present invention, it is further preferred to select a resin with a residual carbon content of 25% to 35% after carbonization, which can better exert the fast charging performance of the carbon-coated product and take into account the initial inventory efficiency of the product. In addition, the resin with this residual carbon content has moderate flowability and good coating uniformity.
[0021] Preferably, the coating method comprises liquid phase coating, and the liquid phase coating method comprises:
[0022] The hard carbon precursor solution is mixed with the graphite matrix material, coated, and dried to obtain a preliminarily coated graphite material.
[0023] The resin coating method in the present invention can be solid phase coating, liquid phase coating, or other conventional coating methods known to those skilled in the art. The liquid phase coating method is preferred because it can improve the uniformity of the coating, obtain a good coating effect, and make the obtained hard carbon coating layer more uniform and dense.
[0024] Furthermore, the specific type of solvent in the hard carbon precursor solution of the present invention can be adaptively selected and adjusted according to the specific type of resin material. The present invention is applicable to any solvent type that does not cause additional reaction of the resin and can dissolve the resin.
[0025] In the present invention, the carbonization temperature is relatively high, preferably selected from 1300 to 1600°C. On the one hand, it can promote the reorganization of the internal structure of the hard carbon after resin carbonization, so that its porosity and specific surface area are improved, thereby improving the embedding and deintercalation efficiency of lithium ions and improving the fast charging performance of the composite graphite material. On the other hand, it can reduce defects and impurities in the material and improve the electrical conductivity, thereby enhancing the cycle stability and rate performance of the composite graphite material; in addition, the thermal stability of the hard carbon is also improved, so that it can still maintain good electrochemical properties in high temperature environments and adapt to a wider range of application scenarios; at the same time, it can also optimize the interface characteristics between the hard carbon and the electrolyte, reduce the interface impedance, and improve the overall performance of the battery.
[0026] Preferably, the carbonization time is 1 to 10 h, for example 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h or 10 h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0027] Preferably, the carbonization atmosphere comprises a protective atmosphere.
[0028] Preferably, the preliminarily coated graphite material is granulated and then carbonized.
[0029] In the present invention, the preliminarily coated graphite material is first granulated, which can better improve the fast charging performance of the material and reduce the expansion of the material during the charging and discharging process; and during the granulation process, there is no need to add an additional binder, and the resin material therein can be used as a coating material and has a certain bonding effect, so that after the granulation process, secondary particles formed by the accumulation of the preliminarily coated graphite material are obtained, thereby generating a porous structure inside, and the pores not only provide a good penetration channel for the electrolyte, but also increase the contact area between the active substance and the electrolyte, promote the rapid embedding and extraction of lithium ions, and improve the transmission rate.
[0030] Preferably, the granulation process is carried out under a protective atmosphere.
[0031] Preferably, the granulation treatment comprises sequentially performing a first granulation heat treatment and a second granulation heat treatment.
[0032] Preferably, the temperature of the first granulation heat treatment is 200-300°C, for example 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C, 270°C, 280°C, 290°C or 300°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0033] Preferably, the time of the first granulation heat treatment is 2 to 3 hours, such as 2 hours or 3 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0034] Preferably, the temperature of the second granulation heat treatment is 500-650°C, for example, 500°C, 510°C, 520°C, 530°C, 540°C, 550°C, 560°C, 570°C, 580°C, 590°C, 600°C, 610°C, 620°C, 630°C, 640°C or 650°C, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0035] Preferably, the time of the second granulation heat treatment is 1 to 5 hours, such as 1 hour, 2 hours, 3 hours, 4 hours or 5 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0036] In the present invention, the granulation treatment is carried out in two stages, which is beneficial to the growth of particle size; and further preferably, the temperature of the first granulation heat treatment is 200-300°C and / or the temperature of the second granulation heat treatment is 500-650°C, thereby achieving effective control of the particle size of the finished product.
[0037] As a preferred technical solution, the preparation method comprises the following steps:
[0038] Mixing and coating a hard carbon precursor resin solution with a graphite matrix material, and drying to obtain a preliminarily coated graphite material, wherein the mass of the resin accounts for 2% to 5% based on the mass of the preliminarily coated graphite material being 100%;
[0039] In a protective atmosphere, the preliminarily coated graphite material is subjected to a first granulation treatment at 200-300° C. for 2-3 hours, and then the temperature is raised to 500-650° C. for a second granulation treatment for 1-5 hours to obtain a granulated product;
[0040] The granulated product is subjected to a carbonization treatment at 1300-1600° C. to obtain the composite graphite material;
[0041] The mass proportion of oxygen atoms in the resin is 15% to 30%, and the amount of residual carbon after carbonization of the resin is 25% to 35%.
[0042] It should also be noted that:
[0043] The graphite matrix material in the present invention is a conventional graphite material that needs to be coated and modified, and the specific type is not particularly limited. For example, it can be natural graphite or artificial graphite, wherein the artificial graphite can be a single graphite particle or a secondary graphite particle. The present invention is applicable to any graphite material that can be obtained within a reasonable range by a person skilled in the art.
[0044] The protective atmosphere in the present invention is an atmosphere that does not participate in the reaction but plays a protective role, for example, it can be a nitrogen atmosphere or an inert gas atmosphere; the inert gas includes argon or helium.
[0045] In a second aspect, the present invention provides a composite graphite material, which is prepared by the preparation method described in the first aspect; the composite graphite material includes a graphite matrix material and a porous hard carbon coating layer coated on the surface of the graphite matrix material.
[0046] Preferably, the composite graphite material is formed by agglomerated particles formed by stacking graphite matrix material particles, the graphite matrix material particles have a porous hard carbon coating layer on their surfaces, and are bonded to adjacent graphite matrix material particles via the porous hard carbon coating layer.
[0047] In the composite graphite material provided by the present invention, graphite matrix materials with hard carbon coating layers are closely stacked, the porous hard carbon coating layers are completely coated, and the stacked particles have good contact with each other.
[0048] Preferably, the specific surface area of the composite graphite material is 1.0 to 4.0 m 2 / g, for example 1m 2 / g, 1.5m 2 / g, 2m 2 / g, 2.5m 2 / g, 3m 2 / g, 3.5m 2 / g or 4m 2 / g, etc., but are not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0049] Preferably, the pore size distribution of the porous hard carbon coating layer in the composite graphite material is 0.5 to 6.0 nm. For example, the endpoint values of the numerical range of the pore size distribution can be 0.5 nm, 1 nm, 1.5 nm, 2 nm, 2.5 nm, 3 nm, 3.5 nm, 4 nm, 4.5 nm, 5 nm, 5.5 nm or 6 nm, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0050] In the present invention, in addition to the porous hard carbon coating layer having a pore structure, inevitably, the graphite matrix material may have a pore structure, and the pore structure in the graphite matrix material originates from the intrinsic defects of the raw material.
[0051] In a third aspect, the present invention provides a battery, comprising the composite graphite material as described in the second aspect.
[0052] The present invention does not impose any special limitation on the battery, and is applicable to any conventional battery type that can use graphite materials. The battery includes but is not limited to lithium-ion batteries, sodium-ion batteries, potassium-ion batteries or zinc-ion batteries, etc., and is preferably used in lithium-ion batteries. The performance of the composite graphite material is better exerted.
[0053] When the composite graphite material provided by the present invention is used in a lithium ion battery, it can be added to the negative electrode of the lithium ion battery as a negative electrode active material. Except for the composite graphite material, the other raw materials and preparation process of the lithium ion battery are all conventional technical solutions, and those skilled in the art can make adaptive selections and adjustments according to actual needs.
[0054] Compared with the prior art, the present invention has the following beneficial effects:
[0055] The preparation method provided by the present invention can provide sufficient active sites to improve the lithium insertion kinetics by selecting a resin in which the mass percentage of specific oxygen atoms is 15% to 30% as the coating material of the graphite matrix material, while not having too many defect sites, so that the obtained composite graphite material of the hard carbon-coated graphite matrix material can take into account both fast charging performance and storage performance without sacrificing other electrochemical properties; the preparation method provided by the present invention is simple to prepare, does not require complicated processing procedures, and is more conducive to large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0056] Figure 1 This is a SEM characterization image of the composite graphite material provided in Example 1 of the present invention.
[0057] Figure 2 This is a SEM characterization image of the artificial graphite matrix material provided in Comparative Example 3 of the present invention. DETAILED DESCRIPTION
[0058] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0059] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" and any variations thereof in this application are intended to cover non-exclusive inclusions.
[0060] In the description of this application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of this application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0061] Example 1
[0062] This embodiment provides a method for preparing a composite graphite material, and the preparation method is as follows:
[0063] A phenolic resin having an oxygen atomic mass ratio of 20% (the amount of residual carbon after carbonization is 30%) is dissolved in tetrahydrofuran to obtain a phenolic resin solution;
[0064] Adding the phenolic resin solution and the artificial graphite matrix material into a mixing pot for liquid phase coating for 1 hour, and then drying at 150° C. to remove the solvent, thereby obtaining a preliminarily coated graphite material, wherein the mass of the phenolic resin is 3.5% of the mass of the preliminarily coated graphite material;
[0065] In a nitrogen atmosphere, the above-mentioned preliminarily coated graphite material is added into a converter for granulation treatment. The granulation treatment is carried out in two stages. In the first stage, the temperature is raised from room temperature to 250° C. for a first granulation heat treatment for 2 hours, and then the temperature is further raised to 500° C. for a second granulation heat treatment for 1 hour to obtain a granulated product. The granulated product is agglomerated particles formed by the accumulation of the preliminarily coated graphite material.
[0066] In a nitrogen atmosphere, the granulated product is subjected to a carbonization treatment at 1300° C. to obtain the composite graphite material;
[0067] The composite graphite material is formed by agglomerated particles formed by stacking graphite matrix material particles. The graphite matrix material particles have a porous hard carbon coating layer on their surfaces and are bonded to adjacent graphite matrix material particles through the porous hard carbon coating layer.
[0068] Example 2
[0069] This embodiment provides a method for preparing a composite graphite material, and the preparation method is as follows:
[0070] A phenolic resin having an oxygen atomic mass percentage of 15% (the carbon residue after carbonization is 35%) is dissolved in tetrahydrofuran to obtain a phenolic resin solution;
[0071] Adding the phenolic resin solution and the artificial graphite matrix material into a mixing pot for liquid phase coating for 1 hour, and then drying at 150° C. to remove the solvent, thereby obtaining a preliminarily coated graphite material, wherein the mass of the phenolic resin is 2% of the mass of the preliminarily coated graphite material;
[0072] In a nitrogen atmosphere, the above-mentioned preliminarily coated graphite material is added into a converter for granulation treatment. The granulation treatment is carried out in two stages. In the first stage, the temperature is raised from room temperature to 300° C. for a first granulation heat treatment for 2 hours, and then the temperature is further raised to 650° C. for a second granulation heat treatment for 1 hour to obtain a granulated product. The granulated product is agglomerated particles formed by the accumulation of the preliminarily coated graphite material.
[0073] In a nitrogen atmosphere, the granulated product is subjected to a carbonization treatment at 1450° C. to obtain the composite graphite material;
[0074] The composite graphite material is formed by agglomerated particles formed by stacking graphite matrix material particles. The graphite matrix material particles have a porous hard carbon coating layer on their surfaces and are bonded to adjacent graphite matrix material particles through the porous hard carbon coating layer.
[0075] Example 3
[0076] This embodiment provides a method for preparing a composite graphite material, and the preparation method is as follows:
[0077] A phenolic resin having an oxygen atomic mass ratio of 30% (the carbon residue after carbonization is 25%) is dissolved in tetrahydrofuran to obtain a phenolic resin solution;
[0078] Adding the phenolic resin solution and the artificial graphite matrix material into a mixing pot for liquid phase coating for 1 hour, and then drying at 150° C. to remove the solvent, thereby obtaining a preliminarily coated graphite material, wherein the mass of the phenolic resin is 5% of the mass of the preliminarily coated graphite material;
[0079] In a nitrogen atmosphere, the above-mentioned preliminarily coated graphite material is added into a converter for granulation treatment. The granulation treatment is carried out in two stages. In the first stage, the temperature is raised from room temperature to 200° C. for a first granulation heat treatment for 3 hours, and then the temperature is further raised to 550° C. for a second granulation heat treatment for 1 hour to obtain a granulated product. The granulated product is agglomerated particles formed by the accumulation of the preliminarily coated graphite material.
[0080] In a nitrogen atmosphere, the granulated product is subjected to a carbonization treatment at 1600° C. to obtain the composite graphite material;
[0081] The composite graphite material is formed by agglomerated particles formed by stacking graphite matrix material particles. The graphite matrix material particles have a porous hard carbon coating layer on their surfaces and are bonded to adjacent graphite matrix material particles through the porous hard carbon coating layer.
[0082] Example 4
[0083] The difference between this embodiment and embodiment 1 is that the resin in this embodiment is epoxy resin.
[0084] The rest of the preparation methods and parameters were the same as those in Example 1.
[0085] Example 5
[0086] The difference between this embodiment and embodiment 1 is that the residual carbon content of the phenolic resin after carbonization in this embodiment is 50%.
[0087] The rest of the preparation methods and parameters were the same as those in Example 1.
[0088] Example 6
[0089] The difference between this embodiment and embodiment 1 is that the residual carbon content of the phenolic resin after carbonization in this embodiment is 10%.
[0090] The rest of the preparation methods and parameters were the same as those in Example 1.
[0091] Example 7
[0092] The difference between this embodiment and embodiment 1 is that this embodiment does not perform granulation treatment, and directly performs carbonization treatment on the preliminarily coated graphite material.
[0093] The rest of the preparation methods and parameters were the same as those in Example 1.
[0094] Example 8
[0095] The difference between this embodiment and embodiment 1 is that the carbonization temperature in this embodiment is 1200°C.
[0096] The rest of the preparation methods and parameters were the same as those in Example 1.
[0097] Example 9
[0098] The difference between this embodiment and embodiment 1 is that the carbonization temperature in this embodiment is 1700°C.
[0099] The rest of the preparation methods and parameters were the same as those in Example 1.
[0100] Comparative Example 1
[0101] The difference between this comparative example and Example 1 is that in the phenolic resin of this comparative example, the mass proportion of oxygen atoms is 10%.
[0102] The rest of the preparation methods and parameters were the same as those in Example 1.
[0103] Comparative Example 2
[0104] The difference between this comparative example and Example 1 is that in the phenolic resin of this comparative example, the mass proportion of oxygen atoms is 40%.
[0105] The rest of the preparation methods and parameters were the same as those in Example 1.
[0106] Comparative Example 3
[0107] The difference between this comparative example and Example 1 is that the composite graphite material in this comparative example is an artificial graphite matrix material that has not been subjected to any coating treatment.
[0108] Figure 1 This is the SEM characterization of the composite graphite material provided in Example 1 of the present invention.
[0109] Figure 2 This is the SEM characterization of the artificial graphite matrix material provided for Comparative Example 3 of the present invention.
[0110] from Figure 1 and Figure 2 It can be seen that before being coated, the artificial graphite matrix material particles exist as single particles with a relatively rough surface, and the exposed defective surface can be clearly seen. After being coated with hard carbon, Figure 1 The composite graphite material in the electrolyte, in which the hard carbon material plays the role of a binder and a coating agent, stacks the single-grain graphite-based material into agglomerated particles, and the particles form an internal porous structure. The pores not only provide a good permeation channel for the electrolyte, but also increase the contact area between the active material and the electrolyte, promote the rapid insertion and extraction of lithium ions, and improve the transmission rate. Figure 2 It can be seen that after being coated with the hard carbon layer, a rounded surface is presented, which can provide a looser transmission channel than graphite, increase the lithium ion diffusion channel, and reduce polarization.
[0111] The composite graphite materials provided in Examples 1-9 and Comparative Examples 1-3 were tested for pore size (i.e., the pore structure of the porous hard carbon coating layer) and specific surface area. The test conditions were as follows: the pore size distribution and specific surface area were determined by gas adsorption and desorption experiments. Specifically, the composite graphite materials were placed at 150°C-300°C and pressure <10 -6 Bar environment for 1h-6h; then nitrogen is introduced at liquid nitrogen temperature to slowly return the pressure to normal pressure and then degas again for 10 -6 Bar, the adsorption-desorption isotherms were obtained by recording the data and calculated according to the density functional theory (DFT) model. The results are shown in Table 1.
[0112] Table 1
[0113]
[0114]
[0115] [Battery preparation and performance testing]
[0116] I. Battery Preparation
[0117] Positive electrode sheet: The positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811), conductive agent carbon black (Super P), and binder polyvinylidene fluoride (PVDF) are fully stirred and mixed in a solvent NMP at a weight ratio of 97.5:1.4:1.1 to form a uniform positive electrode slurry; the positive electrode slurry is evenly coated on the surface of the positive electrode current collector aluminum foil, and after drying and cold pressing, a positive electrode sheet is obtained; wherein the surface density of the positive electrode film layer is 0.178kg / m 2 , compacted density is 3.4g / cm 3 .
[0118] Negative electrode sheet: The composite graphite material provided in Examples 1-13 and Comparative Examples 1-3 were respectively mixed with a binder of styrene-butadiene rubber (SBR), a thickener of sodium carboxymethyl cellulose (CMC-Na), and a conductive agent of carbon black (Super P) in a weight ratio of 96.2:1.8:1.2:0.8 in deionized water and stirred to form a uniform negative electrode slurry; the negative electrode slurry was uniformly coated on the surface of the negative electrode current collector copper foil, and after drying and cold pressing, a negative electrode sheet was obtained; wherein the surface density of the negative electrode film layer was 0.097 kg / m 2 , compacted density is 1.64g / cm 3 .
[0119] Isolation membrane: Porous polyethylene (PE) membrane is used as the isolation membrane.
[0120] Electrolyte: Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent; LiPF6 is uniformly dissolved in the organic solvent to obtain an electrolyte, wherein the concentration of LiPF6 is 1 mol / L.
[0121] Battery assembly: stack and wind the positive electrode sheet, separator, and negative electrode sheet in order to obtain an electrode assembly; place the electrode assembly in an outer package, add the above-mentioned electrolyte, and obtain a secondary battery after packaging, standing, formation, aging and other processes.
[0122] II Performance Test
[0123] The batteries provided in the above-mentioned Examples 1-9 and Comparative Examples 1-3 were subjected to initial efficiency, fast charging, cycle and storage performance tests.
[0124] (a) First effect: the battery is placed in the cabinet for 6 hours; let it stand for 10 minutes; discharge at 0.05C constant current to 5mv and let it stand for 10 minutes; discharge at 50uA constant current to 5mv; let it stand for 10 minutes; discharge at 10uA constant current to 5mv;
[0125] Let stand for 10 minutes; charge at 0.1C constant current to 2V; test the first effect.
[0126] (b) Fast charge: at 25°C, 1. Stand for 6h, discharge at 0.2C to 5mV, stand for 30min, CC-CV charge at 0.2C to 2V, constant voltage to 0.05C, stand for 30min, cycle 2-5 steps for 3 weeks, discharge at different rates 0.05C / 0.1C / 0.33C / 1C / 1.2C to 5mV, stand for 30min, charge at corresponding rates 0.05C / 0.1C / 0.33C / 1C / 1.2C to 2V, stand for 30min. Calculate 1C / 0.05C as the fast charge performance of the material. The larger this ratio is, the better the fast charge performance of the material is.
[0127] (c) Cycle: At 25°C, charge the secondary battery at a constant current of 0.33C to a charge cut-off voltage of 4.4V, then charge at a constant voltage to a current of 0.05C, let stand for 5 minutes, and then discharge at a constant current of 0.33C to a discharge cut-off voltage of 2.8V, and record its initial capacity as C0. Then charge according to the above strategy, discharge at 0.33C, record the discharge capacity Cn of each cycle, until the cycle capacity retention rate (i.e. Cn / C0×100%) is 80%, and record the number of cycles. The more cycles, the higher the cycle life of the secondary battery.
[0128] (d) Storage: The secondary batteries prepared in each embodiment and comparative example were fully charged to 4.2V at a constant current of 0.33C, charged at a constant voltage of 4.2V to 0.05C cut-off, and then discharged to 2.5V at a constant current of 0.33V. The discharge capacity at this time was recorded as C0. Thereafter, they were fully charged to 4.2V at a constant current of 0.33C, charged to 0.05C cut-off at a constant voltage of 4.2V, and then placed in a constant temperature box. After storage at 25°C for 30 days, they were taken out and discharged to 2.5V at 0.33C. Then, they were fully charged to 4.2V at a constant current of 0.33C, charged to 0.05C cut-off at a constant voltage of 4.2V, and then discharged to 2.5V at a constant current of 0.33V. The discharge capacity at this time was recorded as C30. The capacity retention rate (%) of the lithium-ion battery after storage for 30 days = C30 / C0×100%.
[0129] The test results of the above tests are shown in Table 2.
[0130] Table 2
[0131]
[0132]
[0133] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a composite graphite material, characterized in that: The preparation method comprises the following steps: Coating a hard carbon precursor on the surface of a graphite substrate material to obtain a preliminarily coated graphite material, and carbonizing the material to obtain the composite graphite material; Wherein, the hard carbon precursor comprises resin, and the mass proportion of oxygen atoms in the resin is 15% to 30%.
2. The preparation method according to claim 1, characterized in that: Taking the mass of the preliminarily coated graphite material as 100%, the mass of the resin accounts for 2% to 5%; Preferably, the amount of residual carbon in the resin after carbonization is 25% to 35%.
3. The preparation method according to claim 1, characterized in that: The carbonization temperature is 1300-1600° C., and the carbonization time is 1-10 hours.
4. The preparation method according to claim 1, characterized in that: The coating method includes liquid phase coating, and the liquid phase coating method includes: The hard carbon precursor solution is mixed with the graphite matrix material, coated, and dried to obtain a preliminarily coated graphite material.
5. The preparation method according to claim 1 or 3, characterized in that: The preliminarily coated graphite material is granulated and then carbonized; Preferably, the granulation process is carried out under a protective atmosphere.
6. The preparation method according to claim 5, characterized in that: The granulation treatment comprises sequentially performing a first granulation heat treatment and a second granulation heat treatment; Preferably, the temperature of the first granulation heat treatment is 200-300°C, and the time of the first granulation heat treatment is 2-3h; Preferably, the temperature of the second granulation heat treatment is 500-650° C., and the time of the second granulation heat treatment is 1-5 hours.
7. The preparation method according to claim 1, characterized in that: The preparation method comprises the following steps: Mixing and coating a hard carbon precursor resin solution with a graphite matrix material, and drying to obtain a preliminarily coated graphite material, wherein the mass of the resin accounts for 2% to 5% based on the mass of the preliminarily coated graphite material being 100%; In a protective atmosphere, the preliminarily coated graphite material is subjected to a first granulation treatment at 200-300° C. for 2-3 hours, and then the temperature is raised to 500-650° C. for a second granulation treatment for 1-5 hours to obtain a granulated product; The granulated product is subjected to a carbonization treatment at 1300-1600° C. to obtain the composite graphite material; The mass proportion of oxygen atoms in the resin is 15% to 30%, and the amount of residual carbon after carbonization of the resin is 25% to 35%.
8. A composite graphite material, characterized in that: The composite graphite material is prepared by the preparation method according to any one of claims 1 to 7; the composite graphite material comprises a graphite matrix material and a porous hard carbon coating layer coated on the surface of the graphite matrix material.
9. The composite graphite material according to claim 8, characterized in that: The composite graphite material is formed by agglomerated particles formed by stacking graphite matrix material particles, the graphite matrix material particles have a porous hard carbon coating layer on the surface, and are bonded to adjacent graphite matrix material particles through the porous hard carbon coating layer; Preferably, the specific surface area of the composite graphite material is 1.0 to 4.0 m 2 / g, and the pore size distribution of the porous hard carbon coating layer in the composite graphite material is 0.5-6.0 nm.
10. A battery, characterized in that: The battery comprises the composite graphite material according to claim 8 or 9.
Citation Information
Patent Citations
Plumbaginous modifying method and produced modified plumbago
CN101195484A
High-compaction high-rate artificial graphite negative electrode material and preparation method thereof
CN115425206A
Hard carbon / graphene composite negative electrode material for sodium ion battery and preparation method of hard carbon / graphene composite negative electrode material
CN116845222A
High-energy-density fast-charging graphite negative electrode material and preparation method thereof, negative electrode plate and battery
CN117012936A
Graphite negative electrode material and preparation method thereof, negative electrode plate and lithium ion battery
CN117691091A